2018
DOI: 10.14295/cad.cult.cienc.v17i1.1123
|View full text |Cite
|
Sign up to set email alerts
|

ESTRUTURAS PARASITÁRIAS EM ALFACE (Lactuca sativa L.), COMERCIALIZADAS NA FEIRA LIVRE DO MUNICÍPIO DE JARDIM, CEARÁ

Abstract: Resumo: No Brasil, as parasitoses intestinais constituem um dos maiores problemas de saúde pública e são causadas por protozoários e helmintos que podem ser adquiridas de várias maneiras, entre elas através do consumo de hortaliças in natura contendo cistos ou oocistos de protozoários, em especial a alface. O presente estudo visou avaliar o perfil parasitológico das alfaces comercializadas na feira livre do município de Jardim-Ceará. Foram coletadas 26 amostras de alface da variedade crespa comercializadas na … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
(37 reference statements)
0
2
0
1
Order By: Relevance
“…may be caused by organic fertilization, as producers reported using cattle manure as fertilizer. In another study by Pinto et al (2018), which analyzed the level of contamination by parasitic structures in lettuce samples commercialized in street markets in the city of Jardim, Ceará, 80% of the samples were reportedly contaminated by helminth parasitic structures.…”
Section: Discussionmentioning
confidence: 99%
“…may be caused by organic fertilization, as producers reported using cattle manure as fertilizer. In another study by Pinto et al (2018), which analyzed the level of contamination by parasitic structures in lettuce samples commercialized in street markets in the city of Jardim, Ceará, 80% of the samples were reportedly contaminated by helminth parasitic structures.…”
Section: Discussionmentioning
confidence: 99%
“…As parasitoses são doenças relacionadas com a falta de higiene, ausência de saneamento básico e de água tratada (Pinto et al, 2018). As políticas públicas existentes precisam ser consistentes e envolverem educação em saúde, para que amenizem esse tipo de patologia (Lins et al, 2016).…”
Section: Introductionunclassified
“…The detection of parasitic structures in leaves and vegetables demonstrates the potential carrier parasites to humans and, consequently, a risk to public health (Pinto et al, 2018). Draeger et al (2019) have suggested that outbreaks triggered by intestinal parasites often do not have the determination of the parasite specie, in view of a low percentage of species identification (between 25% and 30%) was verified for the cases reported from 2016 to 2017.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of parasitic structures in lettuce produced in Brazil was analyzed in five regions, in farms of production, commercialization area, and their consumption habits, as well as in farm production (Barbosa et al, 2016), horticulture fair (Tiyo et al, 2016), open markets (Medeiros et al, 2019;Ramos et al, 2019;Pinto et al, 2018;Oliveira et al, 2016), supermarkets (Almeida et al, 2016), bistro (Silva et al, 2017), and two or more types of leaves and vegetable commercialization (Ambrozim et al, 2017;Luz et al, 2017;Trevisan et al, 2017;Brauer et al, 2016;Nogueira et al, 2016;Silva et al, 2016). These mentioned studies were carried out in the Southeast, North, Northeast, South and Midwest regions of Brazil, using diagnostic techniques of spontaneous sedimentation or centrifugal -flotation, or the quantitative FLOTAC technique, based on the flotation of eggs and cysts (Pedroso et al, 2020, Ramos et al, 2019.…”
Section: Introductionmentioning
confidence: 99%